2011
DOI: 10.2119/molmed.2010.00166
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Protects against Hepatic Damage Postburn

Abstract: Burn injury causes hepatic dysfunction associated with endoplasmic reticulum (ER) stress and induction of the unfolded protein response (UPR). ER stress/UPR leads to hepatic apoptosis and activation of the Jun-N-terminal kinase (JNK) signaling pathway, leading to vast metabolic alterations. Insulin has been shown to attenuate hepatic damage and to improve liver function. We therefore hypothesized that insulin administration exerts its effects by attenuating postburn hepatic ER stress and subsequent apoptosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Hepatic apoptosis has been recognized as part of the pathological changes after burn injury [28, 29]. High apoptotic cell number after burn injury implicates hepatic damage and impairment to its function.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic apoptosis has been recognized as part of the pathological changes after burn injury [28, 29]. High apoptotic cell number after burn injury implicates hepatic damage and impairment to its function.…”
Section: Discussionmentioning
confidence: 99%
“…A well-established method was used to induce a full-thickness scald burn (13, 14). The treatment groups included sham, sham + LPS, burn, and burn + LPS.…”
Section: Methodsmentioning
confidence: 99%
“…More aggressive control results in suppression of hepatic glucose release, lower systemic glucose levels, decreased incidence of urinary tract infections and mortality when compared to conventional goals of blood glucose <215mg/dL [145]. Animal models have demonstrated that insulin therapy decreases hepatic ER stress, attenuates expression of pro-inflammatory mediators such as IL-6, monocyte chemoattractant protein-1 (MCP-1), and cytokine-induced neutrophil chemoattractant-1 (CINC-1), and reverses structural and functional changes in hepatocyte mitochondria [146]. …”
Section: Clinical Managementmentioning
confidence: 99%